1979
DOI: 10.1136/sti.55.5.357
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of patients with vulvovaginal candidosis. Application of a resistogram method for strain differentiation of Candida albicans.

Abstract: SUMMARY The resistogram method was applied to 420 isolates of Candida albicans obtained from 30 selected patients undergoing treatment for vulvovaginitis. Of these, 16 patients each harboured a particular strain of C. albicans which persisted in the mouth or intestinal tract or both. In three of these patients, this strain persisted in the genital tract, and, in eight patients, it later recolonised the genital tract. Fourteen patients harboured more than one strain of C. albicans: one failed to respond to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Mc Creight and Wamock (3), Wamock et al (7,8) as well as Odds and Abbott (5) found one biotype prevailing largely in the investigated group. Individuals usually harbour the same strains in all the sites investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Mc Creight and Wamock (3), Wamock et al (7,8) as well as Odds and Abbott (5) found one biotype prevailing largely in the investigated group. Individuals usually harbour the same strains in all the sites investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the fact that we obtained the same biotype in the gastrointestinal tract and the vagina in 73.3% of the cases confirms that the gastrointestinal tract, the main yeast reservoir, represents an endogenous source of contamination in many cases (7,17,2,9). Using the resistogram method of strain differentiation, Warnock et al (20) have demonstrated that most patients with genital candidosis also harbored the same strain of C. albicans in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, clinicians often attributed recurrent infection to repeated reinoculation of the genital tract from a persistent intestinal reservoir. This belief was based on the finding that patients often harbour the same strain of C albicans in the genital and intestinal tracts 22 23 24. Two controlled trials showed, however, that oral nystatin treatment, given to reduce intestinal colonisation with C albicans, failed to prevent recurrence of symptoms of vaginal infection 25 26…”
Section: Management Of Recurrent Candidiasismentioning
confidence: 99%
“…Moreover, strain typing methods have indicated that infected partners often harbour identical strains 22 24 28. The role of sexual transmission in vaginal infection is unknown, and topical or oral treatment of the male partner does not seem to prevent recurrence in the woman.…”
Section: Management Of Recurrent Candidiasismentioning
confidence: 99%